Manuscript of Teacher Bertalan Koczuvan from 1879/80 Domovina, ország (deržáva), pravice i dúžnosti purgarov. 1879/80. Koczuván Bertalan, učitelj - Jesenšek, Marko (Slavia Centralis, 2023)
The article discusses the manuscript Domovina, ország (deržáva), práva i dúžnosti purgarov (Homeland, State, Rights and Duties of Citizens). Bertalan Koczuván (Kocuvan), a schoolteacher from Ižakovci, began writing it in 1879/80. This local studies textbook (focusing on local studies and citizens’ duties) was intended for teaching children in the local school. Unfortunately, it remaines unfinished. The manuscript consists of twenty-six calligraphy pages, and is linguistically a supra-dialect as it attempts to follow the norms of uniform literary Slovene (i.e. novoslovenski knjižni jezik). The script is slovenica (Slovene alphabet), with a few spellings of sibilants (c, z, s; č, ž, š) in ogrica (Hungarian alphabet).
Keywords: Prekmurje language, uniform literary Slovene, Slovene standard language, manuscript, textbook, local studies, Bertalan Koczuván (Jernej Kocuvan)